The generic skills learning systematic: Evaluating university students’ learning after complex problem-solving - van Ravenswaaij, Heleen; Bouwmeester, Rianne A. M.; van der Schaaf, Marieke F.; Dilaver, Gönül; van Rijen, Harold V. M.; de Kleijn, Renske A. M. (Frontiers in Education, 2022)
Professionals are increasingly confronted with complex problems that require generic skills. These generic skills are important for a variety of domains and contexts. As the evaluation of such skills can be difficult, this paper reported on the development of the generic skills learning systematic. With this systematic, university students’ self-perceived generic skills learning after following a complex problem-solving course can be evaluated. The systematic was developed by analysing 43 learner reports in an iterative process, in which students described what they had learned during the course. A formative audit was performed to increase and ensure the quality. The Generic Skills Learning Systematic consists of two steps. Step one is identifying students’ learning, where learning is viewed as any described change in generic skills. The changes are called learning categories for which five were distinguished: value, understanding, self-level, intention, and progress. Three checks are described to help with identifying the reported changes of students. In step two, generic skills are identified, using an adapted version of an existing categorization resulting in 36 generic skills in total. Next, the application of the systematic is described and frequency distributions are given to provide insight in the usability of the systematic for educators. The results show that students report learning in a variety of learning categories and generic skills, indicating the broadness of learning in such a complex problem-solving course. In conclusion, educators are advised to rethink the choices made in education regarding the instruction and assessment of students. Broadening our scope of learning and paying attention to the different learning categories can aid the development of the professionals of the future.